2022
DOI: 10.1038/s41598-022-12590-x
|View full text |Cite
|
Sign up to set email alerts
|

Gas chromatography-mass spectrometry-based untargeted metabolomics reveals metabolic perturbations in medullary thyroid carcinoma

Abstract: Medullary thyroid cancer (MTC) is a rare tumor that arises from parafollicular cells within the thyroid gland. The molecular mechanism underlying MTC has not yet been fully understood. Here, we aimed to perform plasma metabolomics profiling of MTC patients to explore the perturbation of metabolic pathways contributing to MTC tumorigenesis. Plasma samples from 20 MTC patients and 20 healthy subjects were obtained to carry out an untargeted metabolomics by gas chromatography–mass spectrometry. Multivariate and u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 53 publications
2
5
0
Order By: Relevance
“…Notably, a significant impact on the biosynthesis of unsaturated fatty acids and fatty acid elongation pathways was recognized (Figure 3D and S3B-C). In concordance, impairments in fatty acid metabolism, purine metabolism, and tri-carboxylic acid cycle were reported in MTC patients compared to healthy controls [42]. In summary, our results demonstrated a profile of signaling pathways altered in human tumors and replicated in our mouse models.…”
Section: Genomic Alteration Landscape In Mouse and Human Tumorssupporting
confidence: 87%
See 1 more Smart Citation
“…Notably, a significant impact on the biosynthesis of unsaturated fatty acids and fatty acid elongation pathways was recognized (Figure 3D and S3B-C). In concordance, impairments in fatty acid metabolism, purine metabolism, and tri-carboxylic acid cycle were reported in MTC patients compared to healthy controls [42]. In summary, our results demonstrated a profile of signaling pathways altered in human tumors and replicated in our mouse models.…”
Section: Genomic Alteration Landscape In Mouse and Human Tumorssupporting
confidence: 87%
“…Conversely, the rapidly growing CGRP-p25OE model harbored mutations that predominantly impacted fatty acid metabolism. This finding is supported by a recent study that demonstrated perturbation of fatty acid metabolism in MTC patients compared to healthy controls [42]. In addition, the overlapping mutated genes between CGRP-p25OE mouse and human tumors clustered pathways associated with fatty acid biosynthesis.…”
Section: Discussionsupporting
confidence: 66%
“…Furthermore, it is prone to lymph nodes invasion and distant metastasis at an early stage; therefore, its prognosis is relatively poor. The ideal survival period of patients with MTC mainly depends on the time from diagnosis to the application of treatment strategies 6–8 . Therefore, early diagnosis and management of MTC are crucial.…”
Section: Introductionmentioning
confidence: 99%
“…The ideal survival period of patients with MTC mainly depends on the time from diagnosis to the application of treatment strategies. [6][7][8] Therefore, early diagnosis and management of MTC are crucial.…”
Section: Introductionmentioning
confidence: 99%
“…Three different deep learning algorithms were explored: Single Layer Perceptron, 1-Hidden Layer Multilayer Perceptron, and 5-Hidden Layer Multilayer Perceptron, with the second one giving the better results (63.3% of correct classifications). Jajin et al 22 considered techniques such as Soft Independent Modelling of Class Analogy (SIMCA) and Orthogonal Partial Least Squares-Discriminant Analysis (OPLS-DA) to discriminate between subjects affected by medullary thyroid cancer and healthy ones, using spectra from GC-MS on plasma samples. By using OPLS-DA, an R 2 parameter (coefficient of determination, with maximum 1) value of 0.925 was obtained.…”
Section: Introductionmentioning
confidence: 99%